Psychological impact of the 2023 Kahramanmaraş earthquakes on non-victims: a cross-sectional study - Metin Çınaroğlu; Eda Yılmazer; Gökben Hızlı Sayar (BMC Public Health, 2025)
Abstract The 2023 Kahramanmaraş earthquakes, with magnitudes of 7.7 and 7.6, caused extensive destruction and psychological distress across southeastern Turkey. This study explores the psychological impact on non-victims, particularly Istanbul residents, focusing on mental health outcomes and coping mechanisms. A cross-sectional survey was conducted from March to May 2024 with 721 participants from various Turkish cities, including a significant portion from Istanbul. Validated psychological scales such as the Beck Depression Inventory-II (BDI-II), Beck Anxiety Inventory (BAI), Warwick-Edinburgh Mental Well-being Scale (WEMWBS), and PTSD Checklist for DSM-5 (PCL-5) measured depression, anxiety, well-being, and PTSD symptoms. Sociodemographic factors like age, gender, occupation, income, education level, and previous earthquake experience were also analyzed. Results showed significant psychological distress among non-victims: 51.9% reported high levels of distress, with 24% meeting PTSD criteria, 30% exhibiting moderate to severe depression, and 28% experiencing significant anxiety. Higher income and education levels correlated with better mental health outcomes. Higher education levels were linked to lower PTSD risk (β = -0.20, p < 0.01) and fewer depression symptoms (β = -0.15, p < 0.05). Higher income was associated with lower depression scores (β = -0.20, p < 0.01) and fewer PTSD symptoms (β = -0.15, p < 0.05). Age positively correlated with well-being (r = 0.68, p < 0.001) and negatively with PTSD symptoms (r = -0.15, p < 0.05). Comparisons with victim studies of major earthquakes, such as the 1995 Great Hanshin-Awaji earthquake, the 1999 Marmara earthquake, the 2008 Wenchuan earthquake, and the 2000 Iceland earthquakes, revealed similar profound psychological impacts. This highlights the need for comprehensive mental health interventions for both direct and indirect exposures. This study underscores the necessity for inclusive mental health strategies to enhance resilience and well-being, ensuring robust recovery after catastrophic events.